Model construction of soybean average diameter and hole parameters of seed-metering wheel based on DEM - Dun, Guoqiang; Mao, Ning; Gao, Zhiyong; Wu, Xingpeng; Liu, Wenhui; Zhou, Cheng (International Journal of Agricultural and Biological Engineering, 2022)
To satisfy the demands of soybean precision sowing, this article starts with statistics of the physical parameters of soybean seeds in Heilongjiang province, China. The filling process of soybean seeds was analyzed, and the ratio relationship between the diameter, depth, chamfer length of seed-metering wheel’s holes and the mean diameter of soybean seeds was determined. EDEM was used to simulate seeding circumstances of hole seed-metering wheel with different holes’ sizes. The hole diameter ratio, hole depth ratio, and chamfer length ratio were the test factors, while the percentage of single multiple and the empty seeds were test indexes. The triple quadratic regression orthogonal rotation combination test was designed, and the mathematical model between test indexes and test factors was established. Results showed that the influence of hole diameter ratio and hole depth ratio was significant (p < 0.01) in the case of single, multiple and empty seed percentage while chamfer length ratio was only significant in single seed percentage compared to multiple and empty seeds percentage (p > 0.05). The chamfer length ratio was 0.15, the hole diameter ratio was 1.63-1.73, the hole depth ratio was 0.81-1.20, the quality of seeding index was more than 90, and multiple and missing indexes were less than 6% and 4%, respectively. The soybean hole wheel seeding device was produced under the optimal parameter combination, to perform a comparative verification test with non-optimized parameters. The test showed anastomotic simulation results, verified the validity of the simulation. The seeding device after optimization expressed the best operating performance, which might satisfy the demands of soybean precision sowing. The study results can provide a theoretical reference for the optimization design of soybean seeding devices. Keywords: agricultural machinery, soybean, seed-metering device, hole seed-metering wheel, EDEM simulation, optimization DOI: 10.25165/j.ijabe.20221501.5914 Citation: Dun G Q, Mao N, Gao Z Y, Wu X P, Liu W H, Zhou C. Model construction of soybean average diameter and hole parameters of seed-metering wheel based on DEM. Int J Agric & Biol Eng, 2022; 15(1): 101–110.